2020
DOI: 10.36290/vnl.2020.096
|View full text |Cite
|
Sign up to set email alerts
|

An incidental finding of pheochromocytoma in a 33-year-old patient with Lynch syndrome

Abstract: 5 Klinika onkologickej chirurgie LF UK a OUSA, Bratislava 6 Oddelenie imunodiagnostiky OUSA a Vysoká škola zdravotníctva a sociálnej práce sv. Alžbety, Bratislava Feochromocytóm je katecholamíny produkujúci neuroendokrinný nádor vychádzajúci z chromafinných buniek drene nadobličky. Záchyt týchto nádorov je mimoriadne dôležitý, pretože sú spojené s vysokou kardiovaskulárnou morbiditou a mortalitou. Vďaka pokrokom v molekulárnej genetike sa vie, že až 35 % feochromocytómov je podmienených geneticky. Lynchov synd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…There are some case reports of pheochromocytoma in patients with Lynch syndrome but not metastatic cases. [15][16][17][18] In those case reports, the primary pheochromocytoma tissue had loss of MMR genes by IHC. This was not the result in the pheochromocytoma metastasis from our patient.…”
Section: Discussionmentioning
confidence: 99%
“…There are some case reports of pheochromocytoma in patients with Lynch syndrome but not metastatic cases. [15][16][17][18] In those case reports, the primary pheochromocytoma tissue had loss of MMR genes by IHC. This was not the result in the pheochromocytoma metastasis from our patient.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was suggested that NEN is part of the extra-colonic tumor presentation in LS; however, not all authors agree [59,60]. Most data on LS-NEN are reported for the gastrointestinal site, an area that is intensively explored due to the high prevalence of CRC [61][62][63].…”
Section: Nen and Mmr/msi Assessmentmentioning
confidence: 99%
“…We identified a single paper (2020) referring to pheochromocytoma in a 33-year-old patient with LS [59]. Interestingly, another report introduced a 57-year-old female with LS first diagnosed with pheochromocytoma by the age of 51.…”
Section: Nen and Mmr/msi Assessmentmentioning
confidence: 99%